Geographic variation in the frequency of isolation and fluconazole and voriconazole susceptibilities of Candida glabrata: An assessment from the ARTEMIS DISK Global Antifungal Surveillance Program - Pfaller, Michael A.; Diekema, Daniel J.; Gibbs, David L.; Newell, Vance A.; Barton, Richard; Bijie, H.; Bille, J.; Chang, Shan-Chwen; Martins, M.L.; Duseh, A.; Dzierzanowska, D.; Ellis, D.; et al. (Elsevier, 2010)
Geographic differences in frequency and azole resistance among Candida glubrata may impact empiric antifungal therapy choice. We examined geographic variation in isolation and azole susceptibility of C. glabrata. We examined 23 305 clinical isolates of C. glabrata during ARTEMIS DISK global surveillance. Susceptibility testing to fluconazole and voriconazole was assessed by disk diffusion, and the results were grouped by geographic location: North America (NA) (2470 isolates), Latin America (LA) (2039), Europe (EU) (12 439), Africa and the Middle East (AME) (728), and Asia-Pacific (AP) (5629). Overall, C. glabrata accounted for 11.6% of 201 653 isolates of Candida and varied as a proportion of all Candida isolated from 7.4% in LA to 21.1% in NA. Decreased susceptibility (S) to fluconazole was observed in all geographic regions and ranged from 62.8% in AME to 76.7% in LA. Variation in fluconazole susceptibility was observed within each region: AP (range, 50-100% S), AME (48-86.9%), EU (44.8-88%), LA (43-92%), and NA (74.5-91.6%). Voriconazole was more active than fluconazole (range, 82.3-84.2% S) with similar regional variation. Among 22 sentinel sites participating in ARTEMIS from 2001 through 2007 (84 140 total isolates, 8163 C. glabrata), the frequency of C. glabrata isolation increased in 14 sites and the frequency of fluconazole resistance (R) increased in 11 sites over the 7-year period of study. The sites with the highest cumulative rates of fluconazole R were in Poland (22% R), the Czech Republic (27% R), Venezuela (27% R), and Greece (33% R). C. glabrata was most often isolated from blood, normally sterile body fluids and urine. There is substantial geographic and institutional variation in both frequency of isolation and azole resistance among C. glabrata. Prompt species identification and fluconazole susceptibility testing are necessary to optimize therapy for invasive candidiasis. (C) 2010 Elsevier Inc. All rights reserved.